ANALISIS TINGKAT BAHAYA EROSI DAN LAHAN KRITIS DI DAERAH ALIRAN SUNGAI RORAYA PROVINSI SULAWESI TENGGARA - La Baco S. La Baco S.; Umar Ode Hasani; Kahirun Kahirun; Abdul Jalil (Universitas Haluoleo, 2018)
ABSTRACTThe degree of erosion hazardand critical land has a link to affect soil conditions. Lands that have a heavy erosion rate tend to be critical which is characterized by low soil productivity. The purpose of this study was to analyze the degree of erosion hazard and critical land in the Roraya watershed. This research was conducted using survey method for primary and secondary datacollection. The results showed that soil erosion rates in the Roraya watershed were dominated by moderate erosion rates (15 - 59 ton/ha/year) and heavy erosion rates (180 - 460 ton/ha/year) of 48,295.10 hectares (33 , 17%) and 37,362.89 hectares (25.66% of the total area of the Roraya watershed). The critical land area in the Roraya watershed is 48,348.06 hectares or 33.21%, while the most critical land area is 1,504.58 hectares or 1.03% of the total area of the Roraya watershed. Keywords: erosion hazard, critical land, Roraya Watershed ABSTRAKTingkat bahaya erosi dan lahan kritis mempunyai keterkaitan untuk mempengaruhi kondisi tanah. Tanah-tanah yang mempunyai tingkat erosi berat cenderung akan menjadi kritis yang dicirikan oleh produktivitas tanah rendah. Tujuan penelitian ini adalah untuk menganalisis tingkat bahaya erosi dan lahan kritis di DAS Roraya. Penelitian ini dilakukan menggunakan metode survei untuk pengambilan data primer dan data sekunder. Hasil penelitian menunjukkan bahwa tingkat erosi tanah di DAS Roraya didominasi oleh tingkat erosi sedang (15 – 59 ton/ha/tahun) dan tingkat erosi berat (180 – 460 ton/ha/tahun) masing-masing seluas seluas 48.295,10 hektar (33,17 %) dan 37.362,89 hektar (25,66 % dari total luas DAS Roraya). Luas lahan yang tergolong kritis di DAS Roraya adalah seluas 48.348,06hektaratau 33,21 %,sedangkan luas lahan sangat kritis adalah 1.504,58hektar atau 1,03 % dari total luas DAS Roraya. Kata Kunci: bahaya erosi, lahan kritis, Daerah Aliran Sungai Roraya